Trauma Informed Behaviour Support A Practical Guide to Developing Resilient Learners - Ayre, Kay; Krishnamoorthy, Govind (Open textbook library., 2020)
If we want to impact the world of children who have experienced trauma then we must change not only ourselves and our classroom, but we must change our schools, our organisations, and our systems of care for children. We must all speak out for these children who have no voice to bring awareness of new educational and mental health approaches to children who will become tomorrow’s failed adults unless they receive our understanding and our help. For whatever reason you have been attracted to this book, you have come to the right place. You may at times put it down and wonder if the challenge is too great, but trust me it is not. If you stay engaged with this book and with a child who has experienced trauma then you will learn new understandings, new ideas and new ways to reach the mind, the heart and the soul of young people who need our support and our love.